Cover Picture: Effects of Mn‐Doping on the Structural and Electrochemical Properties of Na3Ni2SbO6 for Sodium‐Ion Battery. (Batteries & Supercaps 5/2020). Issue 5 (28th April 2020) - Kee, Yongho; Put, Brecht; Dimov, Nikolay; Staykov, Aleksandar; Okada, Shigeto
Abstract : The Front Cover illustrates 2 kinds of synthesized Mn‐doped Na3 Ni2− x Mn x SbO6 layered oxide cathode active materials for Na‐ion battery. The light Mn doped (x=0.25) sample in the left side is enhanced the O'3‐P'3 phase transition kinetics due to the smaller unit‐cell‐volume changes. On the other hand, the heavily doped (x=0.5) sample in the right side suffers from large polarization, corresponding to the reduced two‐phase reaction range and a large unit‐cell‐volume change upon sodium extraction. More information can be found in the Article by S. Okada and co‐workers .